Development Of Data Mining Software Using Association Techniques Based On Apriori Algorithm Method - Mohamad Saefudin; Desy Diana; Hening Hendrato (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Database is a place to store transaction data in an information system that can be developed as a source of knowledge for decision making in an organization. One of the database processing developments is the method of association between data. This technique of processing or extracting data is known as data mining, one of which is association rules. This technique is widely adopted to develop methods, one of which is the Apriori Algorithm Method. This Apriori algorithm runs with the aim of searching for the maximum frequent itemset. This function forms new association rules that are useful for multiplying data into useful information in decision making. Based on the explanation of the Apriori Algorithm, it is then translated into computer software. The software developed is based on cloud computing which can be run online via the web on the internet. The software developed uses the PHP programming language with a MySQL database. Software under development in research can be used in various systems by adjusting the data used. The data mining process using association techniques works according to the number of transaction data items, minimum confidence, minimum support, and number of transactions. The time used in the calculation works according to the minimum value of support and confidence, the association function automatically increases and affects the time used to produce the required information.